2016
DOI: 10.1002/wrna.1354
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into ribosome translocation

Abstract: During protein synthesis, tRNA and mRNA are translocated from the A to P to E sites of the ribosome thus enabling the ribosome to translate one codon of mRNA after the other. Ribosome translocation along mRNA is induced by the universally conserved ribosome GTPase, elongation factor G (EF-G) in bacteria and elongation factor 2 (EF-2) in eukaryotes. Recent structural and single-molecule studies revealed that tRNA and mRNA translocation within the ribosome is accompanied by cyclic forward and reverse rotations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 124 publications
(300 reference statements)
2
76
0
Order By: Relevance
“…Translocation of tRNA•mRNA through the ribosome requires concerted conformational changes within the 40S subunit, and relative to the 60S subunit (Ling and Ermolenko, 2016; Munro et al, 2009; Rodnina and Wintermeyer, 2011; Voorhees and Ramakrishnan, 2013). A large body of work indicates that peptide-bond formation, as well as binding of the translocation GTPase eEF2 (EF-G in bacteria), promote the formation of the so-called hybrid or rotated state, where the small subunit has undergone a counter-clockwise rotation with respect to the large subunit and the head has swiveled, thereby translocating the tRNA on the large subunit (Agirrezabala et al, 2008; Ermolenko et al, 2007; Frank and Agrawal, 2000; Julian et al, 2008; Moazed and Noller, 1989; Rodnina et al, 1997; Spiegel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation of tRNA•mRNA through the ribosome requires concerted conformational changes within the 40S subunit, and relative to the 60S subunit (Ling and Ermolenko, 2016; Munro et al, 2009; Rodnina and Wintermeyer, 2011; Voorhees and Ramakrishnan, 2013). A large body of work indicates that peptide-bond formation, as well as binding of the translocation GTPase eEF2 (EF-G in bacteria), promote the formation of the so-called hybrid or rotated state, where the small subunit has undergone a counter-clockwise rotation with respect to the large subunit and the head has swiveled, thereby translocating the tRNA on the large subunit (Agirrezabala et al, 2008; Ermolenko et al, 2007; Frank and Agrawal, 2000; Julian et al, 2008; Moazed and Noller, 1989; Rodnina et al, 1997; Spiegel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Back rotation, coupled with back-swiveling of the head, completes translocation by moving the anticodon stem loops of the tRNAs on the 40S subunit. GTP hydrolysis by eEF2 links movement of the body and head and ensures directionality (Ermolenko and Noller, 2011; Holtkamp et al, 2014; Ling and Ermolenko, 2016; Taylor et al, 2007). This process is particularly complex, as it requires plasticity on the ribosome, while maintaining the reading frame.…”
Section: (Introduction)mentioning
confidence: 99%
“…Next, GTP-bound elongation factor G (EF-G) binds the ribosome and triggers translocation, promoted by GTP hydrolysis, that shifts all associated tRNAs downstream one site (bringing the base paired mRNA with it). 397 This movement opens the A site for the next aminoacyl-tRNA, and the cycle can repeat after release of EF-G·GDP.…”
Section: Thiopeptidesmentioning
confidence: 99%
“…B 372: 20160180 loops of the tRNAs on the small subunit from A to P and P to E, respectively, together with the advance of the mRNA bound to the tRNAs by one codon. The precise function of GTP hydrolysis on EF-G/eEF2 in this process is still controversial, and it may not be strictly coupled with the second stage of translocation [32].…”
Section: Evidence Of Conformational Dynamics-the Early Daysmentioning
confidence: 99%
“…During this process, the connection between the mRNA †A-tRNA complex and the decoding centre is severed; both tRNAs move to the canonical P/P, E/E sites; the mRNA bound to their anticoon stem-loops is translocated by the length of one codon; the intersubunit rotation is fully reversed and the ribosome is reset to its post-translocational state, a process which involves re-establishment of the physical barrier. The triggering event for this stage of translocation has been thought to be GTP hydrolysis on EF-G, but interpretation of newer results by the Ermolenko group suggests that GTP hydrolysis and the second stage of translocation might not be strictly coupled [32]. The most detailed picture of this stage of translocation was recently obtained by the Blanchard laboratory [91], in which three transient intermediates are identified that can be trapped by antibiotics.…”
Section: Structural Basis Of Intersubunit Motion In the Absence Of Elmentioning
confidence: 99%